Interactive Multimedia And Direct Instruction Elevate Volleyball Mastery For Slow Learners: Multimedia Interaktif Dan Instruksi Langsung Mengangkat Penguasaan Voli Siswa Lamban Belajar - Hanrayani Hanrayani; Ari Iswanto (Academia Open, 2026)
General Background Physical education requires adaptive pedagogical strategies that respond to the varied cognitive and psychomotor developmental needs of students in inclusive settings. Specific Background Slow learners typically process information gradually, struggle with complex directions, and require repeated visual demonstrations and systematic scaffolding to successfully acquire motor competencies. Knowledge Gap While digital visualizations and explicit teaching frameworks individually support skill acquisition, their integrated application remains underexplored for this specific demographic in athletic contexts. Aims This study investigates the application of direct instruction paired with interactive multimedia to advance the volleyball mastery of seventh-grade students. Results Through a three-cycle action research design, mean performance scores progressed significantly from a pre-cycle baseline of 76.18 to 92.43 by the final cycle. Furthermore, classical proficiency levels surged from 20% to a consistent 100%, alongside notable improvements in student classroom engagement and independent practice behaviors. Novelty This research uniquely merges multimedia cognitive theory with explicitly structured sequencing to create an accessible, highly tailored psychomotor learning environment for cognitive learning difficulties. Implications Deploying visually supported, systematic models provides educators with a proven strategy to optimize movement execution and promote active participation among students with special educational needs. Highlights The structured pedagogical intervention raised the average performance scores of participants from 76.18 to 92.43 across three action cycles. Proficiency levels in underhand passing and serving techniques surged from a 20% baseline to a complete 100% attainment. Seventh-grade students with borderline intellectual functioning demonstrated greater classroom engagement and independence during practical physical education tasks. Keywords Interactive Multimedia; Direct Instruction; Slow Learners; Volleyball Mastery; Physical Education